MALDI‐FT‐ICR‐MS for archaeological lipid residue analysis. (5th September 2017) - Oras, Ester; Vahur, Signe; Isaksson, Sven; Kaljurand, Ivari; Leito, Ivo
Abstract: Soft‐ionization methods are currently at the forefront of developing novel methods for analysing degraded archaeological organic residues. Here, we present little‐used soft ionization method of matrix assisted laser desorption/ionization‐Fourier transform‐ion cyclotron resonance‐mass spectrometry (MALDI‐FT‐ICR‐MS) for the identification of archaeological lipid residues. It is a high‐resolution and sensitive method with low limits of detection capable of identifying lipid compounds in small concentrations, thus providing a highly potential new technique for the analysis of degraded lipid components. A thorough methodology development for analysing cooked and degraded food remains from ceramic vessels was carried out, and the most efficient sample preparation protocol is described. The identified components, also controlled by independent parallel analysis by gas chromatography‐mass spectrometry (GC‐MS) and gas chromatography‐combustion‐isotope ratio mass spectrometry (GC‐C‐IRMS), demonstrate its capability of identifying very different food residues including dairy, adipose fats as well as lipids of aquatic origin. The results obtained from experimentally cooked and original archaeological samples prove the suitability of MALDI‐FT‐ICR‐MS for analysing archaeological organic residues. Sample preparation protocol and identification of compounds provide future reference for analysing various aged and degraded lipid residues in different organic and mineral matrices.